The DLSU Board of Trustees unanimously named the three vice presidents for DLSU - De La Salle University, Manila (Animo Repository, 1979)
The DLSU Board of Trustees unanimously named the three vice presidents for DLSU. Incumbent Vice President for Academic Affairs Dr. Paulino Tan retains his position. Bro. Daniel Ortiz serves as Vice President for Administrative Affairs. Bro. J. Benedict acts as Vice President for Planning and Development.